2004
DOI: 10.1007/s11199-004-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Exposure to Muscular Male Models Decreases Men?s Body Satisfaction

Abstract: The current study was designed to examine the effect of exposure to muscular ideal bodies on body satisfaction in men. College men (N = 104) at a medium-sized mid-south university completed the Body Assessment (BA) scale, which measures body satisfaction, before and after exposure to either muscular or nonmuscular advertisements. BA scores were examined using a repeated measures (pre and post) ANOVA with muscularity of image (view images of muscular men vs. view images of average men) as the between-participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 36 publications
3
81
0
3
Order By: Relevance
“…For example, in response to the evidence that thin and muscular media exposure is associated with negative body image, governments, politicians and researchers throughout Australia, Europe, and the United States have called for greater body size diversity in media imagery in order to promote positive body image (Australian Government, 2010;Boyer et al, 2009;Liberal Democrats, 2009;. Research that has investigated the effect of exposure to average-size fashion models (i.e., models with body sizes that are more representative of the general population) supports these recommendations (e.g., Diedrichs & Lee, 2010, in press;Dittmar & Howard, 2004a, 2004bHalliwell & Dittmar, 2004;Halliwell, Dittmar, & Howe, 2005;Lorenzen, Grieve, & Thomas, 2004). These studies have found that viewing average-size female and male models in advertisements is associated with more positive body image among both women and men, in comparison to viewing images of thin and muscular models, or no models.…”
Section: Seeing the Beauty In Everyday People: A Qualitative Study Ofmentioning
confidence: 99%
“…For example, in response to the evidence that thin and muscular media exposure is associated with negative body image, governments, politicians and researchers throughout Australia, Europe, and the United States have called for greater body size diversity in media imagery in order to promote positive body image (Australian Government, 2010;Boyer et al, 2009;Liberal Democrats, 2009;. Research that has investigated the effect of exposure to average-size fashion models (i.e., models with body sizes that are more representative of the general population) supports these recommendations (e.g., Diedrichs & Lee, 2010, in press;Dittmar & Howard, 2004a, 2004bHalliwell & Dittmar, 2004;Halliwell, Dittmar, & Howe, 2005;Lorenzen, Grieve, & Thomas, 2004). These studies have found that viewing average-size female and male models in advertisements is associated with more positive body image among both women and men, in comparison to viewing images of thin and muscular models, or no models.…”
Section: Seeing the Beauty In Everyday People: A Qualitative Study Ofmentioning
confidence: 99%
“…2 Boys' body dissatisfaction has simultaneously increased, 4 and research has demonstrated that exposure to images of extremely muscular models contributes to body dissatisfaction and muscle dysmorphia in young men. [5][6][7] Research regarding media images of women has focused almost exclusively on thinness as the cultural ideal for femininity, 8,9 but there is some indication that modern media figures combine slenderness with a toned and firm look that was not emphasized in previous generations. [10][11][12] Muscle-enhancing behaviors have received considerable attention in the media and popular culture in recent years, as a steady stream of famous male and female athletes have been implicated in legal cases regarding their alleged use of performanceenhancing substances.…”
Section: Discussionmentioning
confidence: 99%
“…As with the large body of literature investigating an array of influences on body dissatisfaction relating to thinness, continued research into media portrayals of muscularity, [5][6][7] as well as interpersonal interactions such as weight-and shape-teasing, or sharing muscle-enhancing substances among peers may be promising avenues for understanding the parallel phenomenon of dissatisfaction with regard to muscularity and unhealthy behaviors aimed at muscle enhancement.…”
Section: Boysmentioning
confidence: 99%
“…As hypothesised, men who viewed the television commercials featuring muscular models reported feeling less attractive or satisfied with their muscle shape and size, compared to the control group. This study demonstrates how comparisons with the muscular models had significant effects on adult men's body image (see also Arbour & Ginis, 2006;Bartlett & Harris, 2008;Lorenzen, Grieve, & Thomas, 2004). Clearly, the images that the media presents as 'ideal' are very influential on male body image.…”
Section: Media Pressure On Menmentioning
confidence: 62%